Factors affecting quality of life in vitiligo patients at Dermatology and Venereology Polyclinic Bali Mandara General Hospital - Handelia Phinari; Betsy Yosia Nadeak; Luh Putu Dina Wahyuni (Bali Dermatology Venereology and Aesthetic Journal, 2022)
Introduction: Vitiligo is a chronic and asymptomatic skin depigmentation disorder due to progressive loss of melanocytes. Vitiligo can affect a patient’s psychological condition that causes disturbances in the quality of life. This study aims to identify factors affecting the quality of life (QoL) in vitiligo patients at Dermatology and Venereology Polyclinic Bali Mandara General Hospital. Research Methods: Cross-sectional study was conducted using Dermatology Life Quality Index (DLQI) questionnaire given to vitiligo patients who came to the Dermatology and Venereology Polyclinic at Bali Mandara General Hospital Denpasar in January 2022. Results: Among the 71 respondents, seven respondents felt no impact, 33 respondents had a small impact, 18 respondents had a moderate impact, and 13 respondents had a very large impact on quality of life. There was a significant relationship between occupation and location of vitiligo with quality of life (p ≤0.05), and partially the location of vitiligo lesions had a significant effect on the quality of life (p ≤0.05). Conclusion: This study shows that vitiligo has a significant impact on quality of life. Relevant counseling and supportive therapy play an important role in the management of vitiligo patients